A Conceptual Model for the Analysis of Investigation Elements in Games - Marques, Pedro; Parreiras, Marcus; Kritz, Joshua; Xexéo, Geraldo (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
This paper presents the 4E conceptual model, developed to formally analyze investigation games from a game design perspective. The model encompasses four components: Exploration, Elicitation, Experimentation, and Evaluation. Grounded Theory was employed as the methodology for constructing the model, allowing for an in-depth understanding of the underlying concepts. The resulting model was then compared to existing literature, and its contributions were thoroughly discussed. Overall, the 4E model presents a comprehensive framework for understanding investigation games elements. It’s application in two real-world scenarios demonstrates its practical relevance.